Student teachers as tutors for children in an inner city school - Levine, Murray; Dunn, Freda; Brochinsky, Steve; Bradley, Jesse; Donlan, Kay (Child Psychiatry & Human Development, 1970)
A tutoring program for first grade inner city children, employing student teachers as tutors, was developed and evaluated. Tutoring had no discernible effects on performance on the Illinois Test of Psycholinguistic Ability. However, tutored children were placed in the highest reading group, and were rated by the regular classroom teacher as having completed the first grade reading series more often than controls. Tutors saw their children as becoming more responsive over time. Classroom teachers rated the tutored children as more competent in the classroom, more confident, and as viewing the classroom as more benevolent. In contrast to controls, student teachers maintained favorable attitudes toward teaching in the inner city, and they claimed to have benefited in practice teaching from their tutoring experience. However, relatively few actually took teaching positions in inner city schools after completing their training. © 1972 Behavioral Publications, Inc.
Keywords: dept.psy